2020
DOI: 10.1016/j.heliyon.2019.e03147
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and lifestyle-related risk factors of obesity and unrecognized hypertension among bus drivers in Ghana

Abstract: Obesity and hypertension are public health problems associated with cardiovascular events worldwide. Bus drivers, whose lifestyle is primarily sedentary and characterized by poor eating habits are at increased risk. This study determined the prevalence and lifestyle-related risk factors of obesity and hypertension among Inter-Regional Metromass Bus Drivers (IRMBDs) in Ghana. This cross-sectional study recruited 527 professional drivers from Metromass Bus stations in Accra and Kumasi Metropolis, Ghana. Structur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
43
0
3

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(52 citation statements)
references
References 54 publications
6
43
0
3
Order By: Relevance
“…The coastal belt studies included one which was conducted in two regions [ 53 ]. One other study was conducted in two regions, one in the coastal and the other in the middle belt [ 54 ]. Fifty-four studies (63.5%) were conducted in urban populations, 12 (14.1%) in rural populations and the remaining 19 (22.4%) in rural populations.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The coastal belt studies included one which was conducted in two regions [ 53 ]. One other study was conducted in two regions, one in the coastal and the other in the middle belt [ 54 ]. Fifty-four studies (63.5%) were conducted in urban populations, 12 (14.1%) in rural populations and the remaining 19 (22.4%) in rural populations.…”
Section: Resultsmentioning
confidence: 99%
“…Seven (8.2%) studies were conducted exclusively in men [ 41 , 48 , 54 , 55 , 65 , 103 , 120 ] and six (7.1%) exclusively in women [ 58 , 78 , 79 , 81 , 89 , 112 ]. In 69 studies that enrolled both sexes, the proportion of females enrolled ranged from 6.3% to 89.0% with a median of 55.3%.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The recent studies reported that the prevalence of hypertension overall in Iran was about 25% [ 34 35 ], and its prevalence in southern province was 27% [ 36 ]. This difference may be related to differences in demographic and lifestyle factors [ 37 ].…”
Section: Discussionmentioning
confidence: 99%
“…Del mismo modo, Anto y cols. hallaron medidas antropométricas la circunferencia abdominal y de cadera donde encontraron que el 19.9% y 19.4% de población presentaban obesidad(35). Al igual que ellos, en nuestro estudio si se encontró asociación entre estas 2 variables.…”
unclassified